HUSBAND'S BEATING OF WIFE: OBJEKTIF REVIEW OF ISLAMIC LAW AND LEGISLATION IN INDONESIA - Ma’sum Anshori (PENA LAW: International Journal of Law, 2023)
The beating of a husband to wife often reflects as an act of domestic violence. The phenomenon that once went viral in Indonesia between a celebrity couple, Lesti Kejora and Rizky Billar, is a form of beating that has become violent. In fact, this unnatural method is contrary to the intentions of the law, both Islamic law and Indonesian law. Therefore, this study is aimed at exploring this subject through phenomenological, psychological, hermeneutic, and contextual approaches, with regard to the husband's beating of the wife. It turns out that in verse 34 of surah al-Nisa', the husband's beating of the wife, who was initially suspected of being a trigger for domestic violence, became the engine of the flying of hidden love and intimacy. This can be achieved if the three stages of coaching in this verse are carried out consistently. Of course, with this hermeneutical interpretation, the intentions of Islamic law and Indonesian law are in the same direction, namely for the creation of a happy family, sakīnah, mawaddah, and raḣmah.